2023
DOI: 10.1002/adom.202300863
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon‐Assisted Directional Infrared Photoluminescence of HgTe Nanocrystals

Abstract: HgTe nanocrystals offer a unique spectral tunability with both absorption and emission covering the near and mid‐infrared as well as the THz window. Nevertheless, a very limited amount of work is dedicated to electroluminescence from this material. An efficient diode not only requires designing a structure that achieves a high electrical efficiency (i.e., efficient electron and hole injections), but also finding a way to efficiently extract the emitted photons. The shift from visible to infrared certainly dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
7
1
Order By: Relevance
“…Enhanced PL has been previously observed with PbS CQDs directly deposited on square metal antenna arrays . This is in contrast to the common observation of quenching on metal surfaces . Here, we still observe enhanced PL even with very thin films of HgTe CQDs (∼25 nm) (Figure S11).…”
Section: Resultscontrasting
confidence: 84%
“…Enhanced PL has been previously observed with PbS CQDs directly deposited on square metal antenna arrays . This is in contrast to the common observation of quenching on metal surfaces . Here, we still observe enhanced PL even with very thin films of HgTe CQDs (∼25 nm) (Figure S11).…”
Section: Resultscontrasting
confidence: 84%
“…In this respect, we note that compact layers of CdSe-CdS/ZnS core–shell NCs were recently shown to obey the local Kirchhoff law in the steady-state, raising the prospect that they follow transient dynamics similar to those evidenced here. On the other hand, experiments on HgTe NC assemblies have shown that their PL is quenched when placed in direct contact with metallic structures, which is the opposite behavior of the PbS NCs investigated in the present study and elsewhere. , It would also be interesting to extend the study to systems in which FRET among emitters is even more pronounced, such as stacks of CdSe nanoplatelets in which the FRET interaction times reach the picosecond scale, allowing photocarrier migration over hundreds of nm from their excitation point …”
Section: Discussionmentioning
confidence: 54%
“…The same approach could be used to design photoluminescent metasurfaces controlling the emitted polarization as reported recently in the context of thermal emission . The method could also be applied to optimize dielectric photoluminescent metasurfaces, ,, which could enable sources with narrower emission cones, as well as electroluminescent metasurfaces. ,, …”
Section: Discussionmentioning
confidence: 92%
“…30 The method could also be applied to optimize dielectric photoluminescent metasurfaces, 23,60,61 which could enable sources with narrower emission cones, as well as electroluminescent metasurfaces. 16,17,62…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation